Lorenz Curves, Size Classification, and Dimensions of Bubble Size Distributions - Sonja Sauerbrei (Entropy, 2009)
Lorenz curves of bubble size distributions and their Gini coefficients characterize demixing processes. Through a systematic size classification, bubble size histograms are generated and investigated concerning their statistical entropy. It turns out that the temporal development of the entropy is preserved although characteristics of the histograms like number of size classes and modality are remarkably reduced. Examinations by Rényi dimensions show that the bubble size distributions are multifractal and provide information about the underlying structures like self-similarity.